2000
DOI: 10.1023/a:1026557315306
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This article concerns nonparametric estimation of association between bivariate failure times. In the presence of independent right censoring, the support for failure time variates may be restricted and measures of dependence over a finite failure time region may be of particular interest. To this end, the reciprocal cross ratio function, weighted by the bivariate failure time density, is proposed as a summary measure of dependence over a failure time region. This 'relative risk' estimator is shown to be consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Related to the cross-ratio, a class of weighted average of local dependence measures have been proposed (Fan, Hsu and Prentice 2000; Fan, Prentice and Hsu 2000). Fan and Prentice (2002) later generalized these dependence measures to accommodate regression effects on the marginal hazard functions.…”
Section: Introductionmentioning
confidence: 99%
“…Related to the cross-ratio, a class of weighted average of local dependence measures have been proposed (Fan, Hsu and Prentice 2000; Fan, Prentice and Hsu 2000). Fan and Prentice (2002) later generalized these dependence measures to accommodate regression effects on the marginal hazard functions.…”
Section: Introductionmentioning
confidence: 99%
“…Although our methodology employs a parametric regression model for the CCSHR, strong modeling assumptions can be avoided by using sufficiently flexible functions of time, such as polynomial functions or regression splines. We have conducted additional simulations, in which data from Frank family (Fan et al, 2000) were considered to check the adequacy of the proposed parametric functions of time. It is shown that the estimated results by using cubic polynomial models agree well with the true time-dependent association, suggesting that cubic polynomial models can yield satisfactory estimates for complex time-dependent association.…”
Section: Discussionmentioning
confidence: 99%
“…Many nonparametric methods have been proposed (Prentice and Cai, 1992; Hsu and Prentice, 1996;Wang and Wells, 2000) over the past twenty years; however, most are subject to complicated estimation or interpretation. Recently, a number of authors (Fan et al, 2000; Bandeen-Roche and Ning, 2008; Cheng and Fine, 2008) have proposed nonparametric estimations of the local conditional hazards ratio (Oakes, 1989), an easily interpreted association measure. However, in this scenario, each association is assumed to be constant over finite time “bins”.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed measure ρ sp ( a ) assesses agreement between the two survival processes within the finite range of [0 , a ]. As with other finite region dependence measures (Fan et al, 2000), the fixed time point a is chosen within the support of the observed survival times. The choice of the time point a may depend on practical interest.…”
Section: Methodsmentioning
confidence: 99%